Improved Light Harvesting in N719 Sensitized Nanocrystalline TiO2 Solar Cells with Coumarin 6 Dye - Pattareeya Kittidachachan; Wichayaporn Soonpanich; Badin Damrongsak (My University, 2014)
Dye-sensitized solar cells (DSSCs) are a promising alternative to conventional semiconductor solar cells due to their ease of fabrication and low manufacturing cost. Ru-based dyes, particularly N719, are the typical dye for DSSC applications. However, N719-based DSSCs have weak absorbance at a wavelength around 440 nm. In this work, we aimed to improve light absorption of the N719-based DSSCs by adding a luminescent dye, Coumarin 6 (C6), into an electrolyte. C6 dye were chosen as it has an absoption and luminescence spectrum complementary to that of N719. The absorption and luminescence spectra of the C6 solution with different dye concentrations, ranging from 1 – 25 M, were investigated in order to find the optimum concentration that is suitbale for the DSSC applications. Moreover, N719 based DSSCs with and without C6 added were fabricated and experimentaly compared. The measurement results show that the N719-based DSSC with C6 dye has the improvement in both short circuit current and device efficiency.
Keywords: Absorbance; Nanocrystalline material; TiO2 Photocatalysis and Solar Cells